Cytogenetic in Vivo Effects of The Aqueous Extract of Raphanus Sativus L. Leaves in Mitosis of the Meristematic Cells of Roots - Mohammed, Rasha Kareem (Iraqi Journal of Science, 2020)
The current study included the preparation of the aqueous extract of Raphanus sativus (Brassicaceae), commonly known as radish which is widely available throughout the world and has been used in folk medicine as a natural drug against many toxicants. The study was designed to evaluate the in vivo cytogenetic activity of the crude aqueous extract of R. sativus on mitosis on Allium cepa root tips as a plant test system. Root tips of A. cepa were tested for four hours with four concentrations of the crude aqueous extract (0.00, 5, 10, 20, 40 mg/ml). The study included a number of cytogenetic analyses such as mitotic index, phase index, and chromosomal aberration. The data showed that this extract led to reducing the mitotic index (MI) to less than 50%. Specifically, when treated with 10 and 40 mg/ml the mitotic index reached 23.72 % and 41.89 %, respectively. This reduction is considered to have toxic and sublethal effects. The extract caused an arrest of the cells at metaphase (c-metaphase) with a high percentage of 80.76% at 5 mg/ml, along with chromosomal aberrations including sticky metaphase, polar deviation, and bridges in anaphase.